Portable damping system for chatter suppression on flexible workpieces. Issue 1 (2019) - Beudaert, X.; Erkorkmaz, K.; Munoa, J.
Abstract: The productivity of the machining operations realised on lightly damped steel welded workpieces is drastically limited by chatter vibrations. This paper introduces a portable system to actively damp out workpiece vibrations. An electromagnetic actuator magnetically clamped onto the workpiece is used both to measure the structural response and to perform active vibration damping. A model-free loop shaping auto-tuning algorithm selects the optimum control parameters. The autonomous controller tuning has critical importance, enabling the machine operator to expediently employ the actuator on different workpieces. Experimental results verify the robustness of the proposed strategy and demonstrate significant productivity increase.